O14.2 Good call! implementation of a regional online and toll-free std clinical consultation program. (13th September 2015) - Fitch, J; Setzer, D; Ryan, S; Finkenbinder, A; Anderson, T; Stewart, T; Burnside, H; Lauzardo, M; Rietmeijer, C
Abstract : Introduction: Following significant changes to the United States healthcare system, community health centres and private providers are providing a greater amount of STI screening, treatment and management that, in the past, would have been performed at public health specialty (STI) clinics. However, general healthcare providers without a background in STIs may be unfamiliar with STI treatment protocols and unusual presentations. To assist healthcare providers in an eight state region, the Denver Prevention Training Centre (PTC) collaborated with the Southeastern National TB Centre (SNTC) to modify their tuberculosis clinical consultation database to serve clinicians performing STI exams. Methods: The Denver PTC and SNTC created an online database and call management system modelled on the TB system. The system tracks and facilitates the clinical consultation process from initiation to completion. A toll free number (1–800–4-STD-CCN) and website (www. STDCCN.org ) were set up. Marketing was done through electronic channels and at healthcare events in the region. Results: The STI clinical consultation system received 2–5 requests a week from clinicians around the region. Unlike the TB system, whose requests have been primarily received through the phone, almost all of the requests for STI consultations came through the online portal. The STI consultation program has been successful both as a means of offering clinical consultation, and, importantly, as a way of tracking the consultations and technical assistance delivered by the training centre. As a result, the STI clinical consultation program will be expanded across the United States in the coming months. The Denver PTC and SNTC are also looking at expanding the process to mobile applications so that consultation can be initiated from mobile devices. Conclusion: Web-based processes can help simplify, facilitate and track the process of STI clinical consultation. Disclosure of interest statement: The Denver PTC and SNTC are funded by the Centres for Disease Control and Prevention, USA. No pharmaceutical grants were received in the development of this study.